Pelaksanaan Bauran Pemasaran Di Bumi Sunda Resto Bandung: - Erwin Setiawan; Sarah Dwi Lestari Nainggolan (JURNAL PARIWISATA VOKASI, 2026)
The restaurant industry in West Java has experienced rapid growth in line with the increasing demand for ready-to-eat food. Business competition among restaurants has intensified, especially in major cities such as Bandung. One restaurant facing this challenge is Bumi Sunda Resto, which has operated for four years with a traditional Sundanese dining concept. Despite various marketing strategies implemented, both online and offline, most visitors come based on word-of-mouth recommendations rather than the restaurant's direct marketing efforts. Observations and customer data indicate that Bumi Sunda Resto's marketing effectiveness remains low, leading to a decline in revenue over a certain period. This study aims to evaluate the implementation of the marketing mix, which includes five key elements: product, price, place, promotion, and physical evidence, also known as the Five Pillars of Marketing. The results of this research are expected to provide recommendations for improving Bumi Sunda Resto’s marketing strategies and enhancing its competitiveness within Bandung’s growing culinary industry. Keywords: Marketing Mix, Promotion, Customer Visits, Revenue,